2019
DOI: 10.1038/s41556-019-0397-z
|View full text |Cite|
|
Sign up to set email alerts
|

The NSL complex maintains nuclear architecture stability via lamin A/C acetylation

Abstract: While nuclear lamina abnormalities are hallmarks of human diseases, their interplay with epigenetic regulators and precise epigenetic landscape remain poorly understood. Here, we show that loss of the lysine acetyltransferase MOF or its associated NSL-complex members KANSL2 or KANSL3 leads to a stochastic accumulation of nuclear abnormalities with genomic instability patterns including chromothripsis. SILAC-based MOF and KANSL2 acetylomes identified lamin A/C as an acetylation target of MOF. HDAC inhibition or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 70 publications
7
70
1
Order By: Relevance
“…Bioinformatic prediction and experimental verification demonstrated that ITGB1-DT physically bound to EZH2 and competitively reduced the binding of EZH2 to ITGB1 promoter. EZH2 is a well-documented epigenetic regulator, which induces H3K27me3 at target gene promoter and represses target gene expression (Karoutas et al, 2019;Karakashev et al, 2020). Consistently, the binding of ITGB1-DT to EZH2 increased ITGB1 expression by reducing the binding of EZH2 to ITGB1 promoter and H3K27me3 levels at ITGB1 promoter.…”
Section: Discussionmentioning
confidence: 86%
“…Bioinformatic prediction and experimental verification demonstrated that ITGB1-DT physically bound to EZH2 and competitively reduced the binding of EZH2 to ITGB1 promoter. EZH2 is a well-documented epigenetic regulator, which induces H3K27me3 at target gene promoter and represses target gene expression (Karoutas et al, 2019;Karakashev et al, 2020). Consistently, the binding of ITGB1-DT to EZH2 increased ITGB1 expression by reducing the binding of EZH2 to ITGB1 promoter and H3K27me3 levels at ITGB1 promoter.…”
Section: Discussionmentioning
confidence: 86%
“…Kansl2 fl/fl mice were generated from mouse embryonic stem cells (mESCs) [tm1a(EUCOMM)Wtsi] obtained from the International Knockout Mouse Consortium ( 54 ) . Kansl3 fl/fl animals were obtained by targeting mESC using a vector obtained from J. Rientjes (Monash, Australia) ( 55 ). Eight- to 12-week-old mice from both sexes were randomly allocated to experimental groups.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we also evaluated the pathway involvement of the proteins associated with the peptide substrates selected for D-TRAINING. Interestingly, most of the proteins harboring the peptides for which KDAC6 displayed the greatest deacetylase activity (>40,000 M -1 s -1 ) either play a structural role or are associated with cellular structural elements (LMNA [53], MYO1G [54], ACTN1 [55], TUBA1A [8,56,57], have chaperone functions (GRP94 [58], HSP90 [10,11]), or are involved in the Rho signaling pathway (ARHGEF1 [59]).…”
Section: Resultsmentioning
confidence: 99%